Pregunta
upstudy study bank question image url

(3) \( 3^{x+1}-2 \cdot 3^{x-1}=21 \) (5) \( 3^{2 x}-4 \cdot 3^{x}+3=0 \) (7) \( 3^{2 x+1}-4 \cdot 3^{x}+1=0 \) (9) \( 3^{x}-4=\frac{45}{3^{x}} \) (11) \( 2^{x}-3 \cdot 2^{3-x}-5=0 \)

Ask by Bowen Chadwick. in South Africa
Feb 21,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Here are the solutions for each equation: 1. **Equation (3)**: \( x = 2 \) 2. **Equation (5)**: \( x = 0 \) or \( x = 1 \) 3. **Equation (7)**: \( x = -1 \) or \( x = 0 \) 4. **Equation (9)**: \( x = 2 \) 5. **Equation (11)**: \( x = 3 \)

Solución

Solve the equation by following steps: - step0: Solve for \(x\): \(3^{x+1}-2\times 3^{x-1}=21\) - step1: Subtract the terms: \(7\times 3^{x-1}=21\) - step2: Divide both sides: \(\frac{7\times 3^{x-1}}{7}=\frac{21}{7}\) - step3: Divide the numbers: \(3^{x-1}=3\) - step4: Set the exponents equal: \(x-1=1\) - step5: Move the constant to the right side: \(x=1+1\) - step6: Add the numbers: \(x=2\) Solve the equation \( 3^{2 x+1}-4 \cdot 3^{x}+1=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(3^{2x+1}-4\times 3^{x}+1=0\) - step1: Factor the expression: \(\left(3^{x}-1\right)\left(3^{x+1}-1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&3^{x}-1=0\\&3^{x+1}-1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=0\\&x=-1\end{align}\) - step4: Rewrite: \(x_{1}=-1,x_{2}=0\) Solve the equation \( 2^{x}-3 \cdot 2^{3-x}-5=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(2^{x}-3\times 2^{3-x}-5=0\) - step1: Factor the expression: \(\left(2^{x}-8\right)\left(2^{x}+3\right)\left(2^{x}\right)^{-1}=0\) - step2: Rewrite the expression: \(\frac{2^{2x}-5\times 2^{x}-24}{2^{x}}=0\) - step3: Cross multiply: \(2^{2x}-5\times 2^{x}-24=2^{x}\times 0\) - step4: Simplify the equation: \(2^{2x}-5\times 2^{x}-24=0\) - step5: Factor the expression: \(\left(2^{x}-8\right)\left(2^{x}+3\right)=0\) - step6: Separate into possible cases: \(\begin{align}&2^{x}-8=0\\&2^{x}+3=0\end{align}\) - step7: Solve the equation: \(\begin{align}&x=3\\&x \notin \mathbb{R}\end{align}\) - step8: Find the union: \(x=3\) Solve the equation \( 3^{2 x}-4 \cdot 3^{x}+3=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(3^{2x}-4\times 3^{x}+3=0\) - step1: Factor the expression: \(\left(3^{x}-3\right)\left(3^{x}-1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&3^{x}-3=0\\&3^{x}-1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=1\\&x=0\end{align}\) - step4: Rewrite: \(x_{1}=0,x_{2}=1\) Solve the equation \( 3^{x}-4=\frac{45}{3^{x}} \). Solve the equation by following steps: - step0: Solve for \(x\): \(3^{x}-4=\frac{45}{3^{x}}\) - step1: Divide the terms: \(3^{x}-4=5\times 3^{2-x}\) - step2: Move the expression to the left side: \(3^{x}-4-5\times 3^{2-x}=0\) - step3: Factor the expression: \(\left(3^{x}-9\right)\left(3^{x}+5\right)\left(3^{x}\right)^{-1}=0\) - step4: Rewrite the expression: \(\frac{3^{2x}-4\times 3^{x}-45}{3^{x}}=0\) - step5: Cross multiply: \(3^{2x}-4\times 3^{x}-45=3^{x}\times 0\) - step6: Simplify the equation: \(3^{2x}-4\times 3^{x}-45=0\) - step7: Factor the expression: \(\left(3^{x}-9\right)\left(3^{x}+5\right)=0\) - step8: Separate into possible cases: \(\begin{align}&3^{x}-9=0\\&3^{x}+5=0\end{align}\) - step9: Solve the equation: \(\begin{align}&x=2\\&x \notin \mathbb{R}\end{align}\) - step10: Find the union: \(x=2\) Here are the solutions for each of the equations provided: 1. **Equation (3)**: \( 3^{x+1}-2 \cdot 3^{x-1}=21 \) - **Solution**: \( x = 2 \) 2. **Equation (5)**: \( 3^{2 x}-4 \cdot 3^{x}+3=0 \) - **Solutions**: \( x_{1} = 0 \), \( x_{2} = 1 \) 3. **Equation (7)**: \( 3^{2 x+1}-4 \cdot 3^{x}+1=0 \) - **Solutions**: \( x_{1} = -1 \), \( x_{2} = 0 \) 4. **Equation (9)**: \( 3^{x}-4=\frac{45}{3^{x}} \) - **Solution**: \( x = 2 \) 5. **Equation (11)**: \( 2^{x}-3 \cdot 2^{3-x}-5=0 \) - **Solution**: \( x = 3 \) If you need further explanations or steps for any of these solutions, feel free to ask!

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve the equations involving exponentials, it’s essential to recognize patterns! In problems like (3) and (5), you can often substitute \( y = 3^x \) or \( z = 2^x \) to simplify expressions. This changes them into polynomial equations, making them more manageable. So, plug in those new variables, simplify, and use methods like factoring or the quadratic formula to find your solutions! When working with exponentials, one common mistake is to forget the properties of exponents, such as \( a^{m+n} = a^m \cdot a^n \). Always be cautious with negative exponents and especially with bases that are fractions or negative numbers. Simplification errors can pop up easy-peasy if you're not careful—so double-check each step!

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad